Protocol to study neuronal membrane proteasome function in mouse peripheral sensory neurons - Emily R. Krueger; Taylor R. Church; Anna Brennan; Fulya Türker; Eric Villalón Landeros (STAR Protocols)
Summary: Neuronal membrane proteasomes (NMPs) are expressed on a subset of somatosensory dorsal root ganglion (DRG) neurons and influence mechanical and pain sensitivity. Here, we present a protocol for studying NMP function in mouse peripheral sensory neurons. We describe steps for procuring and culturing primary DRG neurons. We then detail biochemical and antibody feeding approaches to analyze NMP expression and localization. Finally, we include Ca2+ imaging techniques for investigating NMP function in DRG neurons.For complete details on the use and execution of this protocol, please refer to Villalón Landeros et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.